Integrative Approaches in Education: The Impact of Religion, Philosophy, Psychology, and Sociology on Cooperative and Conflict Dynamics - Sartono Sartono; Jajat Sudrajat; Richad Dedi Syahbudin Afandi; Nandang Koswara (Universitas Muhammadiyah Enrekang, 2024)
This study aims to analyze the dynamics of cooperation and conflict in the context of education based on Religion, Philosophy, Psychology and Sociology (AFPS) in primary and junior secondary schools in Indonesia. A descriptive qualitative approach was used in this study with data collection methods through semi-structured interviews with key personnel, including principals, teachers and students, as well as direct observation in the classroom. The results showed that AFPS-based education successfully increased students' engagement and cooperation through group discussions, collaborative work, as well as the development of critical thinking skills. However, conflict challenges arise as a result of students' different religious backgrounds, philosophical values and academic abilities, which can hinder the learning process if not managed well. Teachers play a key role in facilitating cooperative dynamics and managing conflicts that arise in the classroom. This study also found that factors such as the role of the teacher, school culture, and students' social and cultural backgrounds have a significant effect on the success of AFPS-based education. The implications of this study include the importance of continuous teacher training, managerial support from schools and strengthening inclusive school culture to support open dialogue and effective cooperation in the classroom. The findings are expected to guide the development of a more holistic and inclusive curriculum in Indonesia.